PENANAMAN MODAL ASING PENGANGKATAN BENDA MUATAN KAPAL TENGGELAM (BMKT) DI INDONESIA - Ursula Kristanti Riang Borot; Tiurma Mangihut Pitta Allagan (UNES Law Review, 2022)
In 2021, the government start discussing licensing for foreign investors to search for sunken ship cargo objects (BMKT) under Indonesian waters. This study focuses on normative juridical research by reviewing regulations regarding foreign investment in the lifting of sunken cargo objects (BMKT) in Indonesia and permits for trying to lift sunken cargo objects (BMKT) in the regions. The results obtained are that the regulations have not been specifically regulated, for foreign investment itself it is still running in accordance with the applicable general investment regulations, but specifically for foreign investment in the Lifting of Submerged Ships (BMKT) it is still not optimal and business licensing in The regional government for the Lifting of Sunken Ships (BMKT) for foreign investment is also still not optimally regulated, but Government Regulation No. 6 of 2021 shows that the role of local governments in providing business permits is quite significant through the regional apparatus of the Investment and Integrated Services Agency. One Gate, as well as local governments can provide business licensing matters in accordances with the needs of the region